2007
DOI: 10.1680/geot.2007.57.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge modelling of the effects of soil loading on flexible sewer liners

Abstract: This paper presents an experimental study of the effects of soil loading on large-diameter, close-fitting, non-bonded, flexible sewer liners as typified by ‘cured-in-place pipes’ (CIPP). CIPP is the process whereby a polymeric pipe lining is cast directly against the wall of a deteriorating sewer pipe. The transfer of soil loading to CIPP liners is strongly influenced by the interaction between the existing host pipe and the surrounding soil. In adjusting to deterioration events of the host pipe and possible v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…These include the simple approach of draining heavy fluid to simulate the reduction in stress during excavation or tunnelling (Davis et al, 1980;Bolton & Powrie, 1988), which has been augmented by techniques for in-flight 'concreting' of diaphragm walls (Powrie & Kantartzi, 1996), insertion of props (Richards & Powrie, 1998, Fig. 2(a)), loading of adjacent piles (Choy et al, 2007), and deterioration of sewer linings (Spasojevic et al, 2007).…”
Section: Modern Experimental Methodsmentioning
confidence: 99%
“…These include the simple approach of draining heavy fluid to simulate the reduction in stress during excavation or tunnelling (Davis et al, 1980;Bolton & Powrie, 1988), which has been augmented by techniques for in-flight 'concreting' of diaphragm walls (Powrie & Kantartzi, 1996), insertion of props (Richards & Powrie, 1998, Fig. 2(a)), loading of adjacent piles (Choy et al, 2007), and deterioration of sewer linings (Spasojevic et al, 2007).…”
Section: Modern Experimental Methodsmentioning
confidence: 99%
“…Cluster 7 is plotted in the lower-right corner of Figure 9, which is relatively the "loneliest" cluster compared with other clusters in the figure. This cluster mainly covers the research in the structure analysis domain indicated by the keywords of soil-structure interaction [81][82][83][84][85] and finite element method [86][87][88].…”
Section: Co-occurrence Analysis Of Author Abstractmentioning
confidence: 99%
“…Considering that the final effect of soil voids is the release of support from the pipe, the geometrical shape is the second most important factor. For convenience, the void has been idealized as a simple circular shape in previous papers (Gao et al, 2014;Meguid and Dang, 2009;Moore, 2008;Spasojevic et al, 2007).Based on the calculation results of the void effect and trial calculation (Li and Feng, 2020), the void size was selected with the dimensions of a 10 cm depth, 0.8 m width, and 1.25 m longitudinal length (1/4 of the single pipe length), as illustrated in Figure 2. In this paper, the soil void evenly located under the bell-and-spigot joint was simulated by ''birth-and-death technology'' in the finite element method.…”
Section: Superposition Of Localized Defectsmentioning
confidence: 99%